Virginity Test in Police Recruitment System: Evidence from Indonesia - Manotar Tampubolon (Budapest International Research and Critics University, 2021)
It is difficult for women to become police officers in Indonesia. One of the mandatory requirements is to become a virgin. Women who are no longer virgins cannot pass the selection. However, if the woman's hymen is damaged not because of sexual intercourse but because of an accident, she still hopes to become a police officer. This study aims to examine the virgin criteria as a requirement to become a policewoman in Indonesia. This quantitative study examines the virginity for police admission based on virginity requirements from a human rights perspective and the concept of innocence. Inspired by the idea of purity from Hanne Blank that celibacy does not reflect a known biological necessity and provides no demonstrable evolutionary advantage. This article says that police virginity testing is not essential and makes up discrimination of women's opportunity to become a police officer because there is no correlation between virginity and police duty. This article evaluates this activity performed Indonesian police force from the lights of human rights. It criticizes the policy development specification of Indonesia which is even poor than India and Muslim countries as even in this country women empowerment is prioritized and respected. This country is needed to incorporate changes in this policy.